1959
DOI: 10.1021/jo01091a015
|View full text |Cite
|
Sign up to set email alerts
|

Relative Ease of Hydrogenolysis of Some Organometallic Compounds1

Abstract: The picrate of I was prepared by adding 0.10 g. of I to 5 ml. of a saturated solution of picric acid in chloroform, heating the mixture to boiling, and allowing it to cool slowly.The precipitate was collected, washed with a little chloro-form, and recrystallized from chloroform to give yellow needles melting at 199-200°( dec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…[21] Given the simplicity of these group 2m etal catalysts,w e wondered whether LiAlH 4 ,w hich in imine reduction is normally added stoichiometrically,c ould be catalytically active.A lready in the 1960s,L iAlH 4 was used as ac atalyst for alkyne reduction, [24] however, the very harsh conditions needed (35 mol %c at, 190 8 8C, 80 bar H 2 )d id not encourage follow-up research. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step. Indeed, hydroboration and hydrosilylation reactions were found to be more promising.…”
mentioning
confidence: 99%
“…[21] Given the simplicity of these group 2m etal catalysts,w e wondered whether LiAlH 4 ,w hich in imine reduction is normally added stoichiometrically,c ould be catalytically active.A lready in the 1960s,L iAlH 4 was used as ac atalyst for alkyne reduction, [24] however, the very harsh conditions needed (35 mol %c at, 190 8 8C, 80 bar H 2 )d id not encourage follow-up research. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step. Indeed, hydroboration and hydrosilylation reactions were found to be more promising.…”
mentioning
confidence: 99%
“…[20] We recently reported simple group 2m etal catalysts of the type MN'' 2 (M = Ca, Sr, Ba;N'' = N(SiMe 3 ) 2 ), which operate efficiently under surprisingly mild conditions (1-6 bar H 2 ,8 0 8 8C) and show af air substrate scope and functional-group tolerance. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step. [23] Also the last s-bond metathesis step in the cycle seemed questionable.Acomprehensive calculational study, however, demonstrated that the metal hydride mechanism shown in Scheme 1isfeasible.…”
mentioning
confidence: 99%
“…[2] However, main-group-metal alkyls display lower reactivity toward hydrogen: Examples of such reactions usually imply forcing conditions. [10] We reasoned that the strong polarization of the Al À C bond by the electron-deficient support would ease the heterolytic splitting of H 2 . Prolonged heating of 1 at 400 8C under low H 2 pressure (0.733 bar) afforded material 2.…”
mentioning
confidence: 99%